2022
DOI: 10.1332/239788221x16308608299691
|View full text |Cite
|
Sign up to set email alerts
|

Views of Generation Z regarding care and care careers: a four-country study

Abstract: Globally, life expectancy is increasing, as is the need for effective care responses to chronic health conditions, global emergencies and health disparities. Alongside this is a shortage of skilled caregivers. This four-country qualitative study investigates the views of ‘care’ and ‘care careers’ of Generation Z (the next generation to join the workforce). Four cross-cultural themes emerged: conceptualising care; objects and subjects of care; recognising the challenges of care; and appreciating care work. Disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…We know that career choices for Generation Z (those born 1995–2010, so those entering the labour market now) are influenced by wanting to work for organizations that promote healthy practices and healthy working environments, 26 and research has shown the potential ‘fit’ between Generation Z values and caregiving careers. 27 …”
Section: Discussionmentioning
confidence: 99%
“…We know that career choices for Generation Z (those born 1995–2010, so those entering the labour market now) are influenced by wanting to work for organizations that promote healthy practices and healthy working environments, 26 and research has shown the potential ‘fit’ between Generation Z values and caregiving careers. 27 …”
Section: Discussionmentioning
confidence: 99%
“…"Semi-structured interview form" was used as the data collection tool in this research. In order to prepare the semi-structured interview form, literature was investigated [10][11][12]. The form has a total of 13 questions.…”
Section: Data Collection Toolsmentioning
confidence: 99%